Differential contribution of oral and written modes to lexical, syntactic and propositional complexity in L2 performance in instructed contexts. Issue 2 (1st November 2019) - Vasylets, Olena; Gilabert, Roger; Manchón, Rosa Maria
Abstract : Complexity of L2 output during oral or written task performance has been associated with the process of restructuring; that is, a qualitative change of the internal L2 system by which interlanguage becomes more elaborate and more efficient in communication. While online pressures may restrain the occurrence of restructuring in oral production, the availability of time and visibility of output in writing might create optimal conditions to deploy more complex linguistic structures, with the concomitant interlanguage development. To test these claims, we conducted a study in which we explored if and how the manifestation of lexical, syntactic and propositional L2 complexity was moderated by the mode in which the task was performed. Our participants were 290 instructed L2 learners. They performed orally and in writing a narrative video-retelling task. The analysis revealed moderating task-modality effects on L2 complexity. We found that the written texts displayed higher scores on all the sub-dimensions of syntactic and lexical complexity. Differences were also observed in the way speakers and writers conveyed the propositional content of the task. We interpret these findings as evidence of the facilitating conditions for restructuring during written production in instructed settings and, accordingly, of the language-learning-potential of L2 writing tasks.